1973
DOI: 10.1073/pnas.70.10.2863
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Common Properties of Human β 2 -Microglobulin and the Common Portion Fragment Derived from HL-A Antigen Molecules

Abstract: ABSTRACT11,000-Dalton common portion fragments derived from HL-A antigen molecules were isolated and found to have a significantly high homology to p32-microglobulin in amino-acid composition. Common portion fragments are also very similar to 132-microglobulin with respect to molecular size, charge, and distribution in tissues. Moreover, both are found in the spent culture media of human cell lines and in human plasma and urine.Thus it appears that j62-microglobulin may well be the same substance as the common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
49
0
3

Year Published

1975
1975
1982
1982

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(56 citation statements)
references
References 12 publications
4
49
0
3
Order By: Relevance
“…The molecular-weight data are fully consistent with a tetrameric structure constituted by two types of polypeptide chains. In agreement with previous findings, the present observations demonstrate that the small subunit, ,32-microglobulin, is bound to the large, alloantigenic polypeptide chain by noncovalent interactions only (3)(4)(5)(6)(7)(8)(9)(10)(11). In contrast, the heavy polypeptide chains are held together by disulfide bridge(s).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The molecular-weight data are fully consistent with a tetrameric structure constituted by two types of polypeptide chains. In agreement with previous findings, the present observations demonstrate that the small subunit, ,32-microglobulin, is bound to the large, alloantigenic polypeptide chain by noncovalent interactions only (3)(4)(5)(6)(7)(8)(9)(10)(11). In contrast, the heavy polypeptide chains are held together by disulfide bridge(s).…”
Section: Discussionsupporting
confidence: 81%
“…The large subunit carries the alloantigenic determinants, whereas the small polypeptide chain is invariant. The small subunit has been identified as #2-microglobulin both in man (5,(9)(10)(11) and mouse (7,8). This finding is of particular interest, since previous studies of the amino-acid sequence of 2-microglobulin have shown that this protein is highly homologous to the various IgG heavy and light chain homology regions (12)(13)(14).…”
mentioning
confidence: 84%
“…Am is a small protein (molecular weight 11,800) that was isolated from urine (7). Subsequently, A3~m was found associated with cell surfice antigens of the major histocompatibility locus (8,9). The exact function of A2m is unclear, although recent evidence suggests that the molecule may stabilize the tertiary structure of associated proteins (10).…”
mentioning
confidence: 99%
“…It is found on the surface ofmost nucleated mammalian cells as a component of the major histocompatibility antigens but does not itself associate with the cell membrane (2)(3)(4)(5). The precise function of B2M is unknown but it is thought to play an important role in those immunological phenomena, such as immune responsiveness, immune suppression, T-B cell interaction, and restriction of T-cell specificity, that depend on the expression of histocompatibility antigens (6).…”
mentioning
confidence: 99%
“…The chromosomal location of the gene coding for B2M in other species is not known. Recently, allelic forms of B2M in the mouse have been described, and preliminary studies have suggested linkage between B2m and genes coding for the Ly-4 and H-3 antigens, which have been assigned to mouse chromosome 2 (11,6,12).…”
mentioning
confidence: 99%